Diversity and composition of Trichoptera (Insecta) larvae assemblages in streams with different environmental conditions at Serra da Bocaina, Southeastern Brazil - Henriques-Oliveira,Ana Lucia (2015)
Abstract: Aim The goal of this study is to examine the composition and richness of caddisfly assemblages in streams at the Serra da Bocaina Mountains, Southeastern Brazil, and to identify the main environmental variables, affecting caddisfly assemblages at the streams with different conditions of land use. Methods The sampling was conducted in 19 streams during September and October 2007. All sites were characterized physiographically by application of environmental assessment protocol to Atlantic Forest streams and by some physical and chemical parameters. Of the 19 streams sampled, six were classified as reference, six streams as intermediate (moderate anthropic impact) and seven streams as poor (strong anthropic impact). In each site, a multi-habitat sampling was taken with a kick sampler net. The sample was composed by 20 units, each one corresponded to 1 m2 of collected substrate, corresponding 20 m2 of sampling area. The material was placed in a plastic container (500 µm of mesh), washed, homogenized and sub-sampled. For each stream, 6 subsamples were randomly sorted. Results Were collected 2,113 caddisfly larvae, belonging to 12 families and 28 genera. Hydropsychidae and Leptoceridae were the most abundant families, and Smicridea was the most abundant genus. Sorensen’s index results showed that the streams studied were grouped according to environmental integrity. The Indicator Species Analysis showed only characteristic taxa to reference streams. Canonical Correspondence Analysis showed that caddisfly assemblage was strongly influenced by nitrate concentration, pH and condition of riparian vegetation. Multiple regression analysis indicated significant correlations to five genera with some environmental parameters, besides total abundance of Trichoptera. Conclusions Ours results showed that degree of environmental impact, mainly the nitrate concentration, pH, and condition of cover vegetation acted as a major factor in determining the Trichoptera assemblages present in the stream of the Serra da Bocaina, separating streams along an environmental gradient.